Distinct Haplotype in Non-Ashkenazi Gaucher Patients with N370S Mutation - Amaral, Olga (2012)
A new polymorphism, in intron 7 of glucocerebrosidase gene, has been identified in Gaucher Disease patients. It seems to appear only in Pv1.1- alleles bearing the N370S mutation. This new sub-haplotype was only identified in Portuguese patients, of origins spanning all of the Portuguese continental territory. This finding indicates that, in the Portuguese, mutation N370S has existed in the context of two slightly different haplotypes and thus must be relatively ancient.